2002
DOI: 10.1109/90.993304
|View full text |Cite
|
Sign up to set email alerts
|

The stable paths problem and interdomain routing

Abstract: Abstract-Dynamic routing protocols such as RIP and OSPF essentially implement distributed algorithms for solving the shortest paths problem. The border gateway protocol (BGP) is currently the only interdomain routing protocol deployed in the Internet. BGP does not solve a shortest paths problem since any interdomain protocol is required to allow policy-based metrics to override distance-based metrics and enable autonomous systems to independently define their routing policies with little or no global coordinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
428
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 399 publications
(433 citation statements)
references
References 18 publications
5
428
0
Order By: Relevance
“…We first present a model of interdomain routing and routing policies, based on the standard models in [16] and the Gao-Rexford conditions [13], followed by our threat model for traffic attraction, and finally overview our experimental setup.…”
Section: Model and Methodologymentioning
confidence: 99%
“…We first present a model of interdomain routing and routing policies, based on the standard models in [16] and the Gao-Rexford conditions [13], followed by our threat model for traffic attraction, and finally overview our experimental setup.…”
Section: Model and Methodologymentioning
confidence: 99%
“…Next-hop policies capture an essential feature of interdomain routing as it is currently done: An AS cannot control packet forwarding beyond the neighboring AS to which it initially sends the packets. For this reason, many researchers have studied next-hop policies in order to gain insight into the behavior of interdomain protocols [6,13,24]. Policy consistency, one of the three properties that together comprise our sufficient condition for welfare maximization, is a generalization of next-hop policies.…”
Section: Policy Consistencymentioning
confidence: 99%
“…Policy consistency, one of the three properties that together comprise our sufficient condition for welfare maximization, is a generalization of next-hop policies. Note that, although next-hop policies have been a natural and fruitful topic of research, they are not sufficient for practical use; it has been shown that uncoordinated and unconstrained local configuration of next-hop policies can produce route instability [13,24]. 2.…”
Section: Policy Consistencymentioning
confidence: 99%
“…The policy independence between autonomous systems and the opacity of routing policies outside the autonomous system lead to instabilities. Research on the inconsistencies of BGP-4 has led to the discovery of situations, where the coordinated action of the administrators of more than two routing domains is needed to restore stability in a certain subsection of the Internet [73] and [74]. A routing management overlay, which could be able to detect and avoid this kind of situations would greatly improve the quality of the IPv6 Internet.…”
Section: Multihomingmentioning
confidence: 99%